Angiotensin II type 1 receptor autoantibody blockade improves cerebral blood flow autoregulation and hypertension in a preclinical model of preeclampsia. (1st October 2020) - Duncan, Jeremy W.; Azubuike, Daniel; Booz, George W.; Fisher, Brandon; Williams, Jan M.; Fan, Fan; Ibrahim, Tarek; LaMarca, Babbette; Cunningham, Mark W.
ABSTRACT: Introduction: Women with preeclampsia (PE) and reduced uterine perfusion pressure (RUPP) pre-clinical rat model of PE have elevated angiotensin II type 1 receptor agonistic autoantibodies (AT1-AA) and cerebrovascular dysfunction. Methods: Sprague Dawley rats had RUPP surgery with/without AT1-AA inhibitor ('n7AAc'144 μg/day) osmotic minipumps. Mean arterial pressure (MAP), CBF autoregulation, blood brain barrier (BBB) permeability, cerebral edema, oxidative stress, and eNOS were assessed. Results: 'n7AAc' improved MAP, restored CBF autoregulation, prevented cerebral edema, elevated oxidative stress, and increased phosphorylated eNOS protein in RUPP rats. Conclusion: Inhibiting the AT1-AA in placental ischemic rats prevents hypertension, cerebrovascular dysfunction, and improves cerebral metabolic function.